Milk production chains: a comparative study between two realities - Oliveira, Nilda Souza; Souza Filho, Theophilo Alves; Paes-de-Souza, Mariluce; Riva, Fabiana Rodrigues (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This research aimed to identify the primary´s production competitivity level of milk chain production in the city of Jaru-RO, compared to Patos-MG. This study was based on the proposed competitiveness by Ferraz et al., for which competition should be analyzed starting from the dynamics of the market in which competition occurs, since not only the internal factors are essential for organizations to analyze the competitiveness, but also the structural and systemic factors. As to the method, the research was based on a qualitative approach, whose procedure was the field study. For primary data collection was used an instrument in the form of structured interviews applied to a sample of milk producers in the cities studied. To assess the competitiveness level, the evaluated factors were measured using the weighted average method. Based on analysis of 32 competitiveness factors, the result of research showed that the Jaru´s city has a regular level of competitiveness, while the city of Patos has seen a high level of competitiveness. It was further observed in this research activity is in Jaru technified bit, because it has a flock of low genetic potential in milk production, supplementary feeding deficiency in the herd, poor training of producers, which results generally in low performance. The analysis of enterprise external factors, relevant to the competitive success of this segment also have low evaluation level of competitiveness. Thus, in view of enhancing this system, the Jaru´s milk chain production needs to develop several factors competitive advantages that emerge in this segment, in view of obtaining a better performance in production and in meeting the increasing demands of the consumer market.